Promising ways of attracting foreign investments in Uzbekistan - Doniyorbek Ruziokhunov (Science and Education, 2024)
Uzbekistan, a rapidly developing economy in the heart of Central Asia, is seeking to attract foreign investments to boost its economic growth and modernization. This article explores the government initiatives and reforms that are made to enhance Uzbekistan’s appeal to foreign investors. By analyzing key aspects such as reforms in infrastructure, technological development, strategic initiatives and analyzing international best practices the article gives how the nation has been working on to improve its investment environment for potential investors. The article also evaluates strategies that other countries used to attract foreign investments. Ultimately, the study offers some suggestions that might help raise investment attractiveness.